Optimization of Time and Power Resources Allocation in Communication Systems Under the Industrial Internet of Things - Yang, Ou; Wang, Yang (IEEE access, 2020)
In the Industrial Internet of Things (IIoT), it is an urgent task to reduce power loss and enhance energy efficient through reasonable allocation of resources. Inspired by time slot channel frequency hopping, this paper puts forward a dynamic allocation model for time and power resources. Based on the proposed model, a dynamic resource allocation algorithm was designed to reduce energy consumption. In addition, a power and time allocation algorithm was developed to maximize the energy efficiency of the system. The workflows of the two algorithms were introduced in details. Simulation results show that both dynamic resource allocation algorithm could reduce the energy loss of the communication system, while ensuring the stability of the data queue. The research findings help to promote the performance of communication systems in different scenarios of the IIoT.